OP0100-HPR Does Self-Report of Foot Problems Agree with Clinical Examination in People with Rheumatoid Arthritis?. (9th June 2015) - Wilson, O.S.; Briggs, W.; Hewlett, S.; Pollock, J.; Woodburn, J.; Quest, E.; Swales, C.; Kirwan, J.
Abstract : Background: Data about the frequency of foot problems in rheumatoid arthritis (RA) can be obtained through self-report or clinical examination. The level of agreement between these two approaches has not been established in RA. Objectives: To measure levels of agreement between self-report and clinical examination of foot problems in RA. Methods: A random sample of RA patients who had self-reported foot problems in a questionnaire underwent a structured foot examination and clinical interview conducted by a single observer (podiatrist). Data collected included: patient demographics and clinical characteristics; whether they had accessed foot care (AFC) services (podiatry, orthotics and/or orthopaedics); impact of foot problems (Foot Impact Scale: Impairment/Footwear (FISIF ) and Activities/Participation (FISAP ) subscales); and presence of foot problems on examination. Extent of agreement between self-report and clinical examination was measured by the kappa statistic (k). Results: Of 235 patients invited to participate, 110 (47%) attended; 65 AFC (59%); 77 Female (70%); mean (SD) age 63.1 (11.2) years; median (IQR) disease duration 8.5 (1, 51) years; HAQ 1.25 (0.375, 2.00); FISIF 9 (5, 13); and FISAP 15 (3, 22). The overall frequency of reported and examined foot problems were: toe deformities - 66% and 69%; hallux valgus - 35% and 33%; pes planus - 26% and 56%; callus - 56% and 53%; corns - 12% and 12%; blisters - 5% and 2%; thickened toe-nails - 57% and 45%: ingrown toe-nails - 16% and 15%; joint swelling - 28% and 65%; nodules - 23% and 16%; numbness - 27% and 19%. High agreement occurred for: corns (98%, k=0.913); ingrown toe-nails (97%, k=0.893); and hallux valgus (98%, k=0.959); nodules (92%, k=0.724); callus (84%, k=0.670); toe deformities (86%, k=0.67); and thickened toe nails (80%, K=0.606). Fair agreement was detected for numbness and pes planus (79%, k=0.418 and 76%, k=0.377) but only chance agreement for joint swelling (49%, k<0.01). Conclusions: Overall, high levels of agreement were detected between self-report and clinical examination for many foot problems, suggesting self-report can be utilised with a high degree of confidence. However, levels of agreement for more complex foot problems (e.g. pes planus) were only fair and patients substantially under-reported features of disease activity (e.g. joint swelling), indicating that clinical examination is required for these features. Disclosure of Interest: None declared